Kredibilitas Endorser dan Merek terhadap Minat Beli dengan Sikap terhadap Merek dan Kredibilitas Merek sebagai Intervening pada Produk Lemonilo - Setiana, Gege Arum; Ariyanti, Maya (BUDGETING : Journal of Business, Management and Accounting, 2023)
This research aims to determine the effect of endorser credibility and brand credibility on purchase intentions with attitude towards the brand and attitude towards brand credibility as intervening variables for Lemonilo products. The research method is quantitative with a non-probability sampling technique with a total sample of 271 respondents. The data analysis technique used is SEM-PLS. Based on the research results, it can be concluded that endorser credibility and brand credibility have a positive and significant influence on attitudes towards brand credibility, attitude towards the brand, and purchase intention through the variables attitude towards brand credibility and attitude towards the brand. Keyword: Attitude Towards Brand, Attitude Towards Brand Credibility, Brand Credibility, Endorser Credibility, Purchase Intention.